Transfer of the waterfall source isolate Pectobacterium carotovorum M022 to Pectobacterium fontis sp. nov., a deep-branching species within the genus Pectobacterium - Oulghazi, Said; Cigna, Jérémy; Lau, Yin Yin; Moumni, Mohieddine; Chan, Kok Gan; Faure, Denis (Society for General Microbiology, 2019)
Pectobacterium carotovorum M022 T has been isolated from a waterfall source in Selangor district (Malaysia). Using genomic and phenotypic tests, we re-examined the taxonomical position of this strain. Based on 14 concatenated housekeeping genes (fusA, rpoD, rpoS, acnA, purA, gyrB, recA, mdh, mtlD, groEL, secY, glyA, gapA and rplB), multi-locus sequence analysis revealed that strain M022 T falls into a novel clade separated from the other Pectobacterium species. The in silico DNA-DNA hybridization and average nucleotide identity values were lower than the 70 and 95% threshold values, respectively. In addition, by combining genomic and phenotypic tests, strain M022 T may be distinguished from the other Pectobacterium isolates by its incapacity to grow on D(+)-xylose, L-rhamnose, cellobiose and lactose. Strain M022 T (=CFBP 8629T=LMG 30744 T ) is proposed as the type strain of the Pectobacterium fontis sp. nov. © 2019 IUMS.